2022
DOI: 10.1116/6.0002216
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation on gallium nitride high electron mobility transistors at ON, OFF, and prestressed conditions

Abstract: Radiation damage in electronic devices is known to be influenced by physics, design, and materials system. Here, we report the effects of biasing state (such as ON and OFF) and pre-existing damage in GaN high electron mobility transistors exposed to γ radiation. Controlled and accelerated DC biasing was used to prestress the devices, which showed significant degradation in device characteristics compared to pristine devices under ON and OFF states after γ irradiation. The experiment is performed in situ for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The current density in the ON-mode device degrades two orders of magnitude after 0.1 dpa whereas the OFF-mode device completely loses its functionality. It suggests that ON mode operation is more tolerant to irradiation effects than OFF mode, probably due to a more extended annealing period by self-heating during the ON state, providing a way of self-recovery during irradiation [20]. Furthermore, the application of both drain and gate voltage during irradiation can lead to a modification in the behavior of trapped charges due to the presence of horizontal and vertical electric fields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current density in the ON-mode device degrades two orders of magnitude after 0.1 dpa whereas the OFF-mode device completely loses its functionality. It suggests that ON mode operation is more tolerant to irradiation effects than OFF mode, probably due to a more extended annealing period by self-heating during the ON state, providing a way of self-recovery during irradiation [20]. Furthermore, the application of both drain and gate voltage during irradiation can lead to a modification in the behavior of trapped charges due to the presence of horizontal and vertical electric fields.…”
Section: Resultsmentioning
confidence: 99%
“…Gold heavy ions with mid-level energy (1.5 MeV) and 6.5 × 10 15 gold cm −2 fluence are shown to generate defect clusters that decrease saturation current by four orders of magnitude and cause loss of gate control [12]. Some studies claimed that the presence of an electric field has no impact on incoming ion radiation [19], whereas others show dissimilar behavior in transport properties between ON and OFF conditions [20][21][22][23][24]. Ionizing sources, such as X-ray and 60 Co, have been employed to evaluate the influence of irradiation at various bias conditions in HEMTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have suggested that the presence of an electric field does not affect incoming ion radiation [18], others have shown dissimilar behavior between ON and OFF conditions [27,[29][30][31][32]. To evaluate the influence of irradiation on HEMTs, ionizing sources such as x-rays and 60 Co have been employed under various bias conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Charge buildup can also affect the incoming proton ions and may cause non uniform irradiation dose in the devices. There needs to be more systematic research on low-energy ion irradiation that considers the operating state of devices (ON or OFF state) during irradiation, which can significantly influence their reliability and tolerance to incoming irradiation [29]. In our prior investigation [33], we employed high-energy Au 4+ ions at 2.8 MeV to explore the ON and OFF states of the identical GaN HEMT structure utilized in this study.…”
Section: Introductionmentioning
confidence: 99%